2009
DOI: 10.1007/s00268-009-0207-z
|View full text |Cite
|
Sign up to set email alerts
|

The Lymph Node Ratio Is a Powerful Prognostic Factor of Node‐Positive Colon Cancers Undergoing Potentially Curative Surgery

Abstract: LNR was a robust prognostic indicator for node-positive colon cancers undergoing curative surgery. Because this ratio-based staging was demonstrated to reduce stage migration and to aid in identifying high-risk patients, it should be proposed as a standard tool for colon cancer staging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
4

Year Published

2010
2010
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 41 publications
(98 reference statements)
1
27
0
4
Order By: Relevance
“…Another study by Galizia et al [15] found a similar LNR value (0.18) that was also a strong prognostic indicator in node-positive colon cancer patients undergoing curative surgery. In their group of patients, they demonstrated that an LNR of 0.18 was significant in all subgroups of stage III patients.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Another study by Galizia et al [15] found a similar LNR value (0.18) that was also a strong prognostic indicator in node-positive colon cancer patients undergoing curative surgery. In their group of patients, they demonstrated that an LNR of 0.18 was significant in all subgroups of stage III patients.…”
Section: Discussionmentioning
confidence: 82%
“…In order to overcome this variability and to incorporate the total number of evaluated nodes into the prognostic evaluation system as an additional factor, the lymph node ratio (LNR) was recently suggested as a better prognostic tool for substaging of stage III patients [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] A MEDLINE search was conducted to provide an overview of the literature concerning the prognostic impact of the LNR using the keywords "colorectal cancer" and "lymph node ratio." Of these 21 articles, 7 reports, including the present study, addressed the relationship between the prognostic impact of the LNR and the number of LNs examined.…”
Section: Discussionmentioning
confidence: 99%
“…9 To date, several other studies have reported the prognostic signifi cance of the LNR in colorectal cancer. 3,4,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] It has also been suggested that the LNR can predict survival more accurately than the number of positive LNs. 3,4,11,13,16,19 Furthermore, the application of the LNR, together with the TNM system, may be more predictive of cancer recurrence and survival.…”
Section: Introductionmentioning
confidence: 99%